AI-Driven POS, Adaptable Workload, and Service Culture Influence on Frontline Employee Performance - Kristiana, Yustisia; Goeltom, Vasco Adato Haholongan; Nathalia, Theodosia C. (Pandawan, 2025)
This study investigates the influence of AI-driven perceived organizational support (AI-driven POS), adaptable workload, and service culture on employee performance, with career commitment serving as a mediator. A quantitative approach was used, specifically a cross-sectional survey, involving a sample of 200 frontline hotel employees in Jakarta, selected through purposive sampling. Partial least squares structural equation modeling (PLS-SEM) was used to analyse the relationships between the variables. The findings indicated that AI-driven POS does not have a direct effect on employee performance, whereas adaptable workload and service culture are significant contributors to improving employee performance. Additionally, the study emphasizes the mediating role of career commitment in enhancing the link between adaptable workload, service culture, and employee performance. Career commitment is identified as a crucial motivational factor that encourages employees to surpass expectations. However, the mediation of career commitment between AI-driven POS and employee performance was not supported. Based on these results, the study offers several managerial recommendations for improving frontline employee performance in the hospitality industry.